Measurement of Boundaries and Installation of Boundary Marks for the Function of The Muara Mahat Limited Production Forest in Kampar District, Riau Province - Alexander Ruruh; Muammar Hasan Tuharea; Sarnadi Sarnadi (Journal of Selvicoltura Asean, 2024)
Forest areas that remain with permanent boundaries, namely location, location, area and boundaries that are fixed and definite physically in the field and have legal certainty. To achieve certainty of forest areas, forest area confirmation is carried out, through a long process, namely designation of forest areas, boundary arrangement, mapping and determination of forest areas. The purpose of the Functional Boundary Arrangement is to make the Functional Boundary Mark of the Muara Mahat Limited Production Forest Area in Kampar Regency, Riau Province have legal certainty regarding the location, area and boundaries both administratively and physically in the field. The methods used in general are: Observation, is an activity for observing satellite signals to boundary markers in the Muara Mahat Limited Production Forest Area, Kampar Regency, Riau Province. Receiver, to measure auxiliary points or turning points with a distance of approximately 100 meters. The results of the implementation of the Definitive Boundary Arrangement activity in the form of a map with the title "Map of the Muara Mahat Limited Production Forest Area Boundary Arrangement in Kampar Regency, Riau Province Scale 1: 50,000" which consists of 1 map sheet. In making the map, it is equipped with various symbols according to the information found in the field and contains a situation map on a scale of 1: 1,000,000, signed by the Forest Area Boundary Arrangement Committee. Of the 59 (fifty-nine) boundary markers that are attached, there are measurement points that are carried out using a GPS receiver type GPS receiver type navigation brand Garmin 64SC with an absolute method by averaging with a distance of ± 100 meters. Measurements using GPS Navigation are used as a reference for the measurement route and as a benchmark for the Boundary Pal seal.